Improvement in the Gain of UWB Antenna for GPR Applications by Using Frequency-Selective Surface - Iftikhar Ud Din; Sadiq Ullah; Syeda Iffat Naqvi; Raza Ullah; Shakir Ullah; Esraa Mousa Ali; Mohammad Alibakhshikenari (International Journal of Antennas and Propagation)
In this article, high-gain ultra-wideband (UWB) monopole antenna is presented. The UWB monopole antenna is a semicircular-shaped antenna with a semicircular slot at the top side. The bottom plane consists of partial ground with triangular and rectangular slotted structures to improve the impedance bandwidth of the proposed antenna. In order to enhance gain, a 6×6 metallic reflector (FSS) is placed below the antenna. The performance of the offered design is validated experimentally. The simulated results show resemblance with the measured results. The antenna resonates for the UWB ranging from 3 to 11 GHz. Moreover, the integration of FSS improves the average gain by 4 dB, where peak gain obtained is 8.3 dB across the UWB. In addition, the reported unit cell having dimension of 0.11λ×0.11λ gives wide bandwidth (7.2 GHz) from 3.3 GHz to 10.5 GHz. The performance of the proposed antenna determines its suitability for the modern day wireless UWB and GPR applications.